A study to evaluate the efficacy of cranberry extract supplements in prevention of recurrent urinary tract infections in female patients - P. C., Anju; Gopinath, Syama; Wesley, I. John; G. R., Prasobh (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Recurrence of urinary tract infections (UTI) are either due to re infection or relapse. Overall likelihood of developing UTI is approximately 30 times higher in women than men due to their anatomical peculiarities. The objective was to evaluate efficacy of cranberry extract supplementations in prevention of recurrent UTI in female patients, assess the quality of life of patients, medication adherence of patients and effect of patient counselling. Methods: A prospective observational study was carried out for a period of 6 months and samples were taken from the Urology Department of Cosmopolitan Hospital, Trivandrum, Kerala. The selected patients were administered with cranberry extract supplements after their regular Antibiotic therapy and were observed for recurrence for a period of six months. Three follow ups were taken and the betterment was assessed using the score from prepared proforma. Results: 84 patients were analysed and among them we observed and concluded that 86.9% of patients were free of recurrent infection. Study shows that E. coli was the commonest infectious organism causing UTI. In this study the most commonly observed symptom of UTI was lower abdominal pain and the most common co morbidity was DM. Conclusions: Through this study it was concluded that the cranberry extract supplements significantly reduced the recurrence of UTI in women. Since the antibiotic prophylaxis is having the risk of developing resistance and side effects, the cranberry extract supplements can be suggested as a best alternative to antibiotics in recurrent UTI prophylaxis.